Local Health Units in Portugal: The Influence of Chronic Conditions on Inpatient Readmissions - Óscar Brito Fernandes; Sílvia Lopes; Ana Patrícia Marques; Bruno Moita; João Sarmento; Rui Santana (Karger Publishers, 2020)
Background: In Portugal, a public policy established the Local Health Units (LHUs), merging primary and hospital care providers. LHUs are expected to provide better continuity and coordination of care, thus decreasing the number of unplanned readmissions among those with chronic conditions. This study aims to evaluate the influence of chronic conditions on the risk of readmission at LHUs. Methods: We used inpatient care administrative databases for the years 2002-2014 (n = 1,679,634). We assessed the effects of chronic conditions on the risk of readmission with a difference-in-differences technique, comparing LHUs with a control group. Multivariate Cox regression was used to evaluate time to readmission. Results: The risk of readmission decreased in four LHUs, but significantly only in two. Individuals with more chronic conditions presented a lesser risk of readmission at LHUs, in contrast to those in the control group. Conclusions: After adjusting for the number of chronic conditions and comorbidities, we concluded that LHUs may successfully decrease unplanned readmissions. Several challenges still have to be addressed to achieve a larger and long-lasting effect. Further investigation is needed to account for contextual and organizational effects that may explain differences across LHUs.